Person with disabilities and business sustainability factors in Malaysia: a review of literature / Nur Afiah Ahmad Rofe and Sharifah Zannierah Syed Marzuki - Ahmad Rofe, Nur Afiah; Syed Marzuki, Sharifah Zannierah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2022)
Disability is a natural phenomenon that happens in every country in the world. Just like others, persons with disabilities (PwDs) are also involved in social and economic activities. Unfortunately, not many PwDs are employed. Unfairness still becomes the main problem for PwDs, especially for education and employment. The mistreatment of them seems to be unending. Due to this, the unemployment rate among PwDs keeps on growing including in Malaysia. Multiple solutions have been proposed to reduce this problem. Entrepreneurship is evidenced to have social value as it contributes to socio-economic development. Within this context, multiplying effect is seen to be explicit when entrepreneurial activities are undertaken among vulnerable groups like PwDs. Here, entrepreneurship can help to provide opportunities to create employment for them. The paper elaborates on the factors that help to sustain PwDs in their entrepreneurship venture. It also refers to the Malaysian Plan of Action for Persons with Disabilities 2016-2022, where the equal rights for PwDs to education, employment, and cultural life, the rights to own and inherit property, not to be discriminated against in marriage, children, and not involving them as unwilling subjects in a medical experiment. It is interesting to note that this is a review paper that combines secondary data that include past research, data gathering, and information sought from offline and online materials to come up with logical arguments thus initiating an empirical study in the future. In addition, this paper also aims to support the achievement of the 8th Sustainable Development Goal which is to promote sustained, inclusive, and sustainable economic growth and full employment.